4 shepherds were watching over their flocks and they were commenting on how many sheep they each had.
How many sheep did David have?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let David have "w" sheep. Let Harry have "x" sheep. Let Sam have "y" sheep. Let Peter have "z" sheep. From first condition : − w + 3 w y w z − 3 3 w w + x + y + z Adding 1 and 2, we get : − 2 w z Adding 5 and 3, we get : − 5 w From 1 : − x From 5 : − z Substituting the above two equations in 4, we get : − w + w + 4 + y + y − 4 − 2 w 2 y y Substituting y = 22 in 6, we get : − 5 w 5 w w So, David has 3 sheep = x − 1 = x − 4 ⟶ 1 = w + x + z = y − x − z ⟶ 2 = 3 w = z − 3 ⟶ 3 = 4 × 1 1 = 4 4 ⟶ 4 = y − z − 4 = y − 4 − 2 w ⟶ 5 = y − 7 ⟶ 6 = w + 4 = y − 4 − 2 w = 4 4 = 4 4 = 2 2 = 2 2 − 7 = 1 5 = 3
Simple standard approach.
OMG such a small solution! 😜😂
Log in to reply
LOL, your question was too good to get that.
Log in to reply
Jeez,thank you
Why aren't you able to delete the top part?
Log in to reply
@Rishabh Sood – I dont know
Log in to reply
@Ashish Menon – No prob. Your sol seems to be right anyway
Log in to reply
@Rishabh Sood – Come to slack,I have got something to tell
@Rishabh Sood – Thanks, alright
This requires editing
Log in to reply
I am not able to delete that top part :-(
I did it, i forgot to write "&" , that was the only mistake in LaTeX
Problem Loading...
Note Loading...
Set Loading...
If we denote David by A, Harry by B, Sam by C and Peter by D we can find the answer in the following way. Since A + B + C = D and A + B + C + D = 44, it is easy to see that D has 22 sheep. So A + B + C = 22. We can use this along with the two other facts, A + 3 = B - 1 and C - 3 = 3A, to find that A has 3, B has 7, C has 12 and D has 22. In a little more detail:
A + B + C = 22 (1) A + 3 = B - 1 (2) C - 3 = 3A (3)
Rearrange (3) to give C = 3A + 3 and replace the C in (1) to give A + B + 3A + 3 = 22. Simplified this gives B = 19 - 4A (4). Rearrange (2) to give B - A = 4. Use (4) in the place of B to give 19 - 4A - A = 4 to give A = 3. Now use A to work out B, and then C.